Drug Delivery Strategies for the Management of Attention-deficit/ Hyperactivity Disorder (ADHD): A Case of Differentiated Product Development of Methylphenidate - Kamble, Shubham; Deshmukh, Ganesh; Jain, Paras; Jha, Abhishek; Deshkar, Sanjeevani S. (Recent Advances in Drug Delivery and Formulation, 2025)
ADHD is a common condition that affects many kids in the United States, about 2 to 18 percent of children between 6 and 17 years old. ADHD manifests as hyperactivity, impulsivity, and inattention, impacting various aspects of life. Effective management involves a combination of psychostimulant medication, such as methylphenidate, and behavioral therapy. Modified-release formulations, including chewable tablets, transdermal patches, and osmotic-controlled release tablets, offer improved treatment adherence and overall quality of life. Understanding the pathophysiology involves neuroimaging studies that reveal alterations in brain regions rich in dopamine receptors. Methylphenidate, a common ADHD medication, works by inhibiting dopamine reuptake, thereby increasing extracellular dopamine levels. Different drug delivery systems, such as extended-release chewable tablets, transdermal patches, and OROS formulations, provide diverse options for individual needs. The advent of innovative formulations like methylphenidate hydrochloride extended-release oral suspension (Quillivant ER) and methylphenidate hydrochloride multilayer extended-release capsules (Aptensio XR) addresses challenges in pediatric medication administration. Recent additions like the orally disintegrating tablet (Cotempla X-ODT) offer convenience and flexibility. Understanding the pharmacokinetics, pharmacodynamics, and benefits of these formulations enhances the ability to tailor ADHD treatment to individual patient needs.
Keywords: formulation development